BRIGHT ASTEROIDS IN THE RED SEA - AN EMERGING PATHOGEN CANDIDA HAEMOLUNII: ARE AZOLES THE TREATMENT OPTION? - T, Sanyuktha; Rao, Pooja; B, Keerthiraj; M, Radhakrishna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This is a case study of a 15-year-old female who on chemotherapy and central line catheter-related bloodstream candidemia presented with recurrent episodes of candidemia, was febrile and breathless. She was diagnosed of Candida haemulonii fungemia. Echinocandins was started as this species of Candida is usually resistant to the commonly used antifungal agents. On treatment, the patient was afebrile and discharged. Keywords: Candida haemulonii, Candidemia, Case report, Emerging pathogen Â